AUDIT OPERASIONAL PADA FUNGSI PRODUKSI (STUDI KASUS : PT. Ispat Panca Putera) - Dhimadhanu, Ridor; Alauddin, Akhmad (GEMA EKONOMI, 2018)
Steel industry is a strategic industry that exists in Indonesia, thedevelopment of this industry is growing rapidly along with thedevelopment of domestic infrastructure, the steel industry is also classifiedinto the manufacturing industry where raw materials will be processedinto finished products to be sold to customers. The most important part inthe manufacturing industry is the operational part, especially in theproduction function. This research was conducted at PT Ispat PancaPutera which aims to know the implementation of operational audit onproduction function, management of applied management in the company,and measure the level of effectiveness, efficiency, economization ofproduction function. The research approach uses a qualitative approachthat intends to understand the phenomenon of what is experienced by thesubject of research, with data collection methods used are passiveparticipation observation, documentation, and interviews. In the audit ofthis production function that measures the efficiency, effectiveness, andeconomics of the company, in 2017 the average percentage decreaseoccurred in the third quarter so that in the fourth quarter the company isrequired to increase. The conclusion of this research is the level of efiensi,effectiveness, and economization in the production section is very good,and control of company management also very good, existence of masterplan of production which become reference in determining target whichwill be reached every month so that it can progressively increaseefficiency level, effectiveness, and economization on the part ofproduction.ÃƒÆ’Ã†â€™ÃƒÂ¢Ã¢â€šÂ¬Ã…Â¡ÃƒÆ’Ã¢â‚¬Å¡Ãƒâ€šÃ‚Â DOI : 10.5281/zenodo.3475674